A brief review on physiological commitment in basketball: An interpretative key - Altavilla, G.; Raiola, G. (Journal of Human Sport & Exercise, 2019)
The physiological commitment is widely investigated because is the basis of physical training methods and sports sciences. Every sport has a characteristic pattern of exercise and range of exercise intensities which determine the energy requirements in the sport. The review of the literature and scientific documents was conducted through the use of several databases: PubMed, MedLine, Google Scholar. Several studies carry out a lot of data and then they have applied to team sports such as soccer, basketball, handball, rugby. Performance analysis studies show that each team sport has the own and different characteristics and has unique profiles because the indicators are different. The physiological commitment may be different in the several situations analysed and be dependent on the type of mechanics of the running. The results, relative at the intensity, fatigue resistance and ability of to cover wide distances, in varied way, by basketball players during matches, can substantially affect basketball theory and practice. The purpose of this work is to analyse and evaluate the physiological commitment required of basketball players (linear and varied running with and without dribble), trying to extract relevant information from a series of research carried out in different countries of the world, for an interpretative analysis of theoretical and documental results.